Optimasi Penyerapan Rhodamin B Menggunakan Biosorben Dari Kulit Buah Matoa Dengan Metode Batch - Mutia, Nuraini Cut; Nasra, Edi; Kurniawati, Desy (Periodic, 2023)
Research Optimizing the absorption of rhodamine b dye has been carried out using the batch method with biosorbent from matoa skin. This study aims to determine the optimum conditions of each parameter used and determine the value of the absorption capacity of matoa skin against Rhodamine B. Variations in particle size used for biosorption of rhodamine b were 106 µm, 150 µm, 250 µm, and 425 µm, while variations in contact time ranged from 30 minutes to 180 minutes with an interval of 30 minutes. The result of measuring the maximum wavelength of rhodamine b dye using a UV-Vis spectrophotometer is 554 nm with an absorbance value of 0.245. For variations in particle size, the optimum adsorption capacity was 71.08 mg/g at 106 µm, while for variations in contact time, the optimum adsorption capacity was 72.85 mg/g at 150 minutes. In this study, matoa peel has the potential to be used as an alternative biosorbent in the absorption of rhodamine b.